ISOLASI DAN IDENTIFIKASI SENYAWA ANTIOKSIDAN DAUN KESEMEK (Diospyros kaki Thunb.) DENGAN METODEDPPH (2,2-DIFENIL-1-PIKRILHIDRAZIL) - Isnindar Isnindar; Subagus Wahyuono; Erna Prawita Setyowati (Majalah Obat Tradisional, 2011)
Antioxidant is a substance which in small concentrations can significantly inhibit or prevent the oxidation of the substrate. One plant is efficacious as an antioxidant is the persimmon (Diospyros kakiThunb.) where is cultivated widely in East Asia, Spain and Indonesia. In the search for natural antioxidant compounds, have been studied isolation and identification of antioxidant compound of persimmon leaves (DiospyroskakiThunb.) using DPPH (2,2-diphenyl-1-pikrilhidrazil) method. The extraction of persimmon leaves was carried out by maceration method with wasbenzen. Extracts obtained by evaporating the solvent wasbenzenon a rotary evaporator and were then re-macerated with methanol. Antioxidant activity of extracts was evaluated with DPPH 0.2% method. Active extract was partitioned with chloroform, methanol, distilled water and tested for antioxidant activity by DPPH 0.2% method. The active compound was purified byPTLC and the purified active isolates was then confirmed by TLC. The antioxidant activity (IC50) active isolates were analyzed using spectrophotometry. Analysisof active isolates resulted the antioxidant activity (IC50) of 100.00 ug / ml. UV-Vis spectrum of the active isolates showed absorption at λmax 285 and 401 nm. Infrared spectra (KBR) showed absorption at 3446 cm-1 (OH), 2926 cm-1 (CHaliphatic), 1456 cm-1 (CH2), 1384 cm-1 (CH3), 1255 cm-1, and 1115 cm-1 (C-0-C), 1631 cm-1 (C=Caromatic). GC-MS spectra gave two peaks with retention time 11.408 minutes with a similarity index of 79.243% with the molecular ion (M•)+ appeared at m/z 178, 163, 147. These spectra are expected to be methyl eugenol. Furthermore, the peak with retention time 12.982 minutes with a similarity index of 20.757%, producing a mass spectrum with molecular ion peaks (M•)+appeared at m/z 192, 177, 161. These spectra are expected to be myristicin compound.